Learning JavaScript - Powers, Shelley (O'Reilly, 2006)
As web browsers have become more capable and standards compliant, JavaScript has grown in prominence. JavaScript lets designers add sparkle and life to web pages, while more complex JavaScript has led to the rise of Ajax -- the latest rage in web development that allows developers to create powerful and more responsive applications in the browser window. Learning JavaScript introduces this powerful scripting language to web designers and developers in easy-to-understand terms. Using the latest examples from modern browser development practices, this book teaches you how to integrate the language with the browser environment, and how to practice proper coding techniques for standards-compliant web sites. By the end of the book, you'll be able to use all of the JavaScript language and many of the object models provided by web browsers, and you'll even be able to create a basic Ajax application.